RESPON INDONESIA MENGHADAPI KEBIJAKAN RENEWABLE ENERGY DIRECTIVE (RED) UNI EROPA TERHADAP PRODUK CPO CRUDE PALM OIL (CPO) INDONESIA - Jesika Amelia; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Palm oil is a commodity that plays an important role in national income and Indonesia's sustainable development. However, amid the popularity of palm oil, various trade barriers emerged, especially from the European Union. Through the Renewable Energy Directive (RED) policy, Palm Oil Resolution and Anti-Dumping Policy aimed at Indonesian CPO products. For the Indonesian government, this policy is used as a tool to protect the vegetable oil market in the European Union by inhibiting and gradually stopping the use of CPO. The theory used in this study is from the perspective of liberalism and the theory of international trade, where countries trade with the aim of achieving production economies of scale. The research method uses qualitative research with descriptive analysis, with data collection techniques namely secondary data. Through interview research and library research (Library Research). The results of this study indicate that the Indonesian Government's response in dealing with these obstacles is to file a lawsuit through the WTO, carry out oil palm diplomacy and increase commitment to sustainability through ISPO certificates. Keywords: RED, Palm Oil Resolution, BMAD, Indonesia, European Union, ISPO, WTO.